Analisis Strategi Pemasaran Pada Coffee Shop (Studi Kasus Pada Misi Kopi Kota Tebing Tinggi) - Husni Sinulingga, Muhammad; Tryana Sembiring, Meilita; Iskandarini, Iskandarini (Journal of Accounting and Finance Management, 2024)
Misi Kopi is a coffee shop in Tebing Tinggi that offers both coffee and non-coffee beverages, along with snacks for customers. The business utilizes both traditional and digital marketing strategies to boost sales. This study aims to evaluate Misi Kopi’s marketing strategy through a SWOT analysis (strengths, weaknesses, opportunities, and threats) in comparison to other coffee shops in Tebing Tinggi City. The research follows a descriptive qualitative approach, with a sample of 10 informants. Data collection was conducted through interviews and questionnaires, while SWOT analysis was used for data analysis. The findings show that Misi Kopi has significant internal and external factors that allow it to compete successfully in the local market. The IE matrix places Misi Kopi in the first quadrant, indicating its competitive advantage. The study also highlights the need for Misi Kopi to enhance its product quality and leverage social media marketing to further promote its offerings